The impact of constipation on pediatric emergency department: a retrospective analysis of the diagnosis and management - Gatto, Antonio; Curatola, Antonietta; Ferretti, Serena; Capossela, Lavinia; Nanni, Lorenzo; Rendeli, Claudia; Chiaretti, Antonio (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Functional constipation (FC) represents 95% of pediatric constipation cases. The aim of this study was to assess the prevalence of Functional Constipation in children admitted to Pediatric Emergency Department (ED) with acute abdominal pain, the demographic factors associated, the use of imaging exams and laboratory tests.Methods: A retrospective observational study was conducted on 4100 medical records of children aged 0 to 18 years.Results: Among children with abdominal pain, 11.3% of them had a discharge diagnosis of constipation and 45.5% underwent imaging exams. Most of children (93.9%) were discharged with home therapy and 6.5% of patients needed of additional visits. In ED 6.7% of patients underwent enema, 45.2% were discharged with indication to perform it at home.Conclusions: FC is a medical condition that could be managed in the outpatient setting, even if we observed a significant percentage of cases in ED. We observed over-utilization of radiologic tests, whereas the diagnosis should be clinical.